Therapeutic effect of selective interleukin-2-inducible tyrosine kinase inhibitor in orbital fibroblasts from patients with Graves’ orbitopathy - Yeonjung Yoon; Hyun Young Park; Min Kyung Chae; Sun Young Jang; Jin Sook Yoon (Endocrine Journal)
Interleukin-2-inducible tyrosine kinase (ITK) is a crucial cytoplasmic protein in the T-cell signaling pathway. Here, we aimed to demonstrate the anti-inflammatory effect of the selective IL-2-induced tyrosine kinase inhibitor BMS-509744 (BMS) on Graves’ orbitopathy (GO) in an in vitro model. ITK mRNA expression in orbital tissues from GO and normal controls was compared using real-time polymerase chain reaction (RT-PCR) and immunohistochemistry. Primary cultured orbital fibroblasts from each group were pretreated with BMS and stimulated with interleukin (IL)-1β to induce inflammatory reaction. ITK mRNA expression was evaluated using western blotting, and inflammatory cytokine production and downstream transcription factor expression were analyzed after pretreatment with BMS. ITK mRNA expression in GO tissues was significantly higher than that in normal control tissues. After stimulation with IL-1β, ITK phosphorylation significantly increased in both GO orbital and normal control tissues. BMS inhibited IL-1β-induced IL-8 expression in the GO orbital fibroblasts. BMS pretreatment significantly suppressed NF-κB phosphorylation in both GO and normal controls. The selective ITK inhibitor attenuates proinflammatory cytokine production and proinflammatory transcription factor phosphorylation in in vitro model of GO.